1990
DOI: 10.1136/bmj.300.6721.374
|View full text |Cite
|
Sign up to set email alerts
|

Open access gastroscopy: too much to swallow?

Abstract: 14 Horn M\EC, Dick MC, Frost B, et al. Neonatal screening for sickle cell diseases in Camberwcll: results and recommendations of a two year pilot study. BrMedJ 1986;292:737-40. 15 Rowley PT. Newborn screening for sickle cell disease. Benefits and burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 4 publications
1
30
0
Order By: Relevance
“…However, evidence from open access endoscopy has consistently demonstrated that primary care physicians use such services appropriately [19,20] . Furthermore, a trial of open access echocardiography considered only 12% of referrals as 'inappropriate' [21] .…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence from open access endoscopy has consistently demonstrated that primary care physicians use such services appropriately [19,20] . Furthermore, a trial of open access echocardiography considered only 12% of referrals as 'inappropriate' [21] .…”
Section: Discussionmentioning
confidence: 99%
“…8,12,113,149,[263][264][265][266][267][268][269][270][271][272][273][274][275][276][277] As the yield from endoscopy varied widely with case-mix in these studies, a range only was used for comparison. As later studies have shown lower rates of PUD and cancer, the aim for these was at the lower end of this range, and at the upper end of the range for oesophagitis.…”
Section: Validationmentioning
confidence: 99%
“…Importantly, the yield for this new technology is comparable to that for existing endoscopic techniques. For all indications, gastroscopy and colonoscopy have reported yields of between 19.5% and 72% [16][17][18] and 5% and 65% [19][20][21][22] . The reported change in management after gastroscopy and colonoscopy of 7%-58% is also comparable to that for CE in this study [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Demand was highest in patients with OGB (iron deficiency anemia, n = 104 patients; overt bleeding, n = 55 patients) and suspected active Crohn's disease (n = 68 patients). The average number of investigations per patient prior to CE was 4.3 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. These investigations were in the form of upper gastrointestinal endoscopy, colonoscopy, push enteroscopy, small bowel studies, radionuclear scans, bone marrow aspirates, angiography, computed tomography, diagnostic laparoscopy, and even laparotomy.…”
Section: Indications For Capsule Endoscopymentioning
confidence: 99%